The Networked Media Economy and the Indian Gilded Age - Fitzgerald, Scott (2020)
This chapter examines how the rapid growth of the networked media economy has become aligned with the broader development of digital platforms in India. Given debates over new forms of economic dependency arising from the power of digital platforms, the chapter critically explores a Braudelian model of global capitalism in the context of the specific state-capital relationships that have fostered an ‘Indian Gilded Age’. It analyses the development of Jio Platforms, India’s largest telecommunications firm and a subsidiary of Reliance Industries Limited (RIL), which is owned and controlled by the country’s wealthiest individual, Mukesh Ambani.